Contemporarising Tagore and the world - Ahmed, Imtiaz; Dubey, Muchkund; Sikri, Veena (The University Press in association with Indian Council for Cultural Relations, Dept. of International Relations, University of Dhaka, 2013)
Papers presented at the International Conference on 'Contemporarising Tagore and the World', held at Dhaka during 29th April to 1st May 2011.